Development of a System and Method for Automated Isolation of Stromal Vascular Fraction from Adipose Tissue Lipoaspirate - Swathi SundarRaj; Abhijeet Deshmukh; Nancy Priya; Vidya S. Krishnan; Murali Cherat; Anish Sen Majumdar (Stem Cells International)
Autologous fat grafting for soft tissue reconstruction is challenged by unpredictable long-term graft survival. Fat derived stromal vascular fraction (SVF) is gaining popularity in tissue reconstruction as SVF-enriched fat grafts demonstrate improved engraftment. SVF also has potential in regenerative medicine for remodeling of ischemic tissues by promoting angiogenesis. Since SVF cells do not require culture expansion, attempts are being made to develop automated devices to isolate SVF at the point of care. We report development of a closed, automated system to process up to 500 mL lipoaspirate using cell size-dependent filtration technology. The yield of SVF obtained by automated tissue digestion and filtration (1.17 ± 0.5 × 105 cells/gram) was equivalent to that obtained by manual isolation (1.15 ± 0.3 × 105; p = 0.8), and the viability of the cells isolated by both methods was greater than 90%. Cell composition included CD34+CD31− adipose stromal cells, CD34+CD31+ endothelial progenitor cells, and CD34−CD31+ endothelial cells, and their relative percentages were equivalent to SVF isolated by the manual method. CFU-F capacity and expression of angiogenic factors were also comparable with the manual method, establishing proof-of-concept for fully automated SVF isolation, suitable for use in reconstructive surgeries and regenerative medicine applications.